Investigation on design and control aspects of a new autonomous mobile agricultural fruit harvesting robot. (September 2022) - Khare, Divyansh; Cherussery, Sandra; Mohan, Santhakumar
This paper focuses its attention on investigating the mechanical design and control aspects of a new autonomous mobile agricultural robot being developed for the purpose of automated harvesting of fruits in plantations. The paper goes from discussing the need of automated harvesting of fruits and the problems involved to conceptualizing the design of such a robot and ends with a brief discussion on the control aspects of the robot.